2015
DOI: 10.1002/acr.22494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age at Menopause on Disease Presentation in Early Rheumatoid Arthritis: Results From the Canadian Early Arthritis Cohort

Abstract: Objective. Studies suggest that hormonal states affect disease characteristics in women with rheumatoid arthritis (RA). This study investigated how age at menopause affects disease in women presenting with early RA. Methods. This was a cross-sectional study of postmenopausal women with early RA under age 65 years at time of enrollment in the Canadian Early Arthritis Cohort. RA-related disease characteristics in women who had early age at menopause (EM; age at menopause <45 years) were compared to those who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
0
34
3
Order By: Relevance
“…The third hormonal shift is during menopause, when estrogen levels decrease. It has been hypothesized that the menopausal transition is related to an increased risk of RA, but the literature has been scarce , Early menopause (age ≤44 years) was previously associated with RF‐negative RA in one study , but with RF positivity in a study of a group of women with early RA . The disparity between our study and the study by Wong et al could be due to different study designs.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The third hormonal shift is during menopause, when estrogen levels decrease. It has been hypothesized that the menopausal transition is related to an increased risk of RA, but the literature has been scarce , Early menopause (age ≤44 years) was previously associated with RF‐negative RA in one study , but with RF positivity in a study of a group of women with early RA . The disparity between our study and the study by Wong et al could be due to different study designs.…”
Section: Discussioncontrasting
confidence: 69%
“…A previous case–control study nested within a community‐based health survey reported that early menopause was associated with an increased risk of RA, and that the risk of RF‐negative RA was much more pronounced (odds ratio [OR] 5.0, 95% confidence interval [95% CI] 1.72–14.51) than the risk of RF‐positive RA (OR 1.98, 95% CI 0.91–4.31) . In a Canadian cohort of early RA cases, early age at menopause (age <45 years) was associated with RF positivity with an OR of 2.2 (95% CI 1.3–3.8) . If increased RA risk at the time of menopause is due to hormonal fluctuation, then postmenopausal hormone therapy (PMH) could theoretically reduce RA risk.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this possibility, the incidence of rheumatoid arthritis among women rises in the immediate postmenopausal years, and premature menopause is associated with higher disease risk. Postmenopausal hormone supplementation appears to afford minimal, if any, protection perhaps because IgG glycosylation represents only one of many factors associated with disease risk (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no effect was found related to onset of menarche, oral contraceptive use or hysterectomy/oophorectomy, though those women who underwent later menopause (after age 51 years) were at decreased risk of developing RA compared to those who underwent menopause at or below age 45. However, a recent study, in which a group of 534 patients in a Canadian inception cohort of RA patients were divided into an “early menopause” (mean age 38.5 years) and “usual menopause” group (mean age 51.7 years), the age of RA disease onset was found to be similar between the groups [54]. Furthermore, the early menopause patients were more likely to be rheumatoid factor positive, a characteristic of the disease that is known to impart increased risk of erosive joint disease as well as extra-articular, systemic manifestations (e.g., vasculitis, interstitial lung disease).…”
Section: Reviewmentioning
confidence: 99%